Wide-field retinal optical coherence tomography with wavefront sensorless adaptive optics for enhanced imaging of targeted regions - Polans, James; Keller, Brenton; Carrasco-Zevallos, Oscar M.; LaRocca, Francesco; Cole, Elijah; Whitson, Heather E.; Lad, Eleonora M.; Farsiu, Sina; Izatt, Joseph A. (Biomedical optics express, 2017)
The peripheral retina of the human eye offers a unique opportunity for assessment and monitoring of ocular diseases. We have developed a novel wide-field (>70°) optical coherence tomography system (WF-OCT) equipped with wavefront sensorless adaptive optics (WSAO) for enhancing the visualization of smaller (<25°) targeted regions in the peripheral retina. We iterated the WSAO algorithm at the speed of individual OCT B-scans (~20 ms) by using raw spectral interferograms to calculate the optimization metric. Our WSAO approach with a 3 mm beam diameter permitted primarily low- but also high- order peripheral wavefront correction in less than 10 seconds. In preliminary imaging studies in five normal human subjects, we quantified statistically significant changes with WSAO correction, corresponding to a 10.4% improvement in average pixel brightness (signal) and 7.0% improvement in high frequency content (resolution) when visualizing 1 mm (~3.5°) B-scans of the peripheral (>23°) retina. We demonstrated the ability of our WF-OCT system to acquire non wavefront-corrected wide-field images rapidly, which could then be used to locate regions of interest, zoom into targeted features, and visualize the same region at different time points. A pilot clinical study was conducted on seven healthy volunteers and two subjects with prodromal Alzheimer's disease which illustrated the capability to image Drusen-like pathologies as far as 32.5° from the fovea in un-averaged volume scans. This work suggests that the proposed combination of WF-OCT and WSAO may find applications in the diagnosis and treatment of ocular, and potentially neurodegenerative, diseases of the peripheral retina, including diabetes and Alzheimer's disease.